THE IMMUNOMODULATORY EFFECT OF PHYLLANTHUS NIRURI L. EXTRACT ON ANTIBODY TITERS IN NEWCASTLE DISEASE-VACCINATED BROILERS - Daniel Halim; Ida Bagus Kade Suardana; Tjokorda Sari Nindhia; Tri Komala Sari; Ni Luh Eka Setiasih; Anak Agung Sagung Kendran (Buletin Veteriner Udayana, 2025)
Newcastle Disease (ND) remains a major threat to the poultry industry, and while vaccination is essential, the immune response can be inconsistent. This study evaluated the potential of Phyllanthus niruri L. (meniran) extract as an immunomodulator to enhance the humoral immune response in broilers post-ND vaccination. A total of 30 one-day-old broilers, vaccinated against ND, were divided into three treatment groups: P0 (control, no extract), P1 (extract at 5 mg/kg BW/day via drinking water from day 3 to 17), and P2 (extract from day 3 to 24). Antibody titers were measured using the Hemagglutination Inhibition (HI) test and analysed with ANOVA using SPSS software. The results demonstrated that meniran extract significantly increased antibody titters compared to the control (P<0.05). Group P2, which received the extract until day 24, achieved the highest mean titter (6.1 log2 HI units), followed by P1 (4.4 log2) and the control P0 (4.0 log2). Data analysis confirmed a positive relationship between the duration of extract administration and antibody levels. In conclusion, Phyllanthus niruri L. extract is an effective immunomodulator that significantly enhances the ND vaccine-induced antibody response in broilers, with a longer administration period yielding a more robust effect.